Adherence to oral antineoplastic therapy among patients with advanced or metastatic non-small cell lung cancer: a noninterventional, prospective study - Irene Mangues-Bafalluy; Beatriz Bernardez; José Manuel Martínez-Sesmero; Andres Navarro-Ruiz; Maria Teresa Martín-Conde; Ana Rosa Rubio-Salvador; Judith Rius-Perera; Marta Gilabert-Sotoca; Marta Domínguez López; Angel Callejo Mellén (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose We aimed to evaluate adherence to oral antineoplastic therapy (OAT) in patients with locally advanced or metastatic non-small cell lung cancer (NSCLC) and its potential relationship with several clinical outcomes. Methods Observational, prospective, multicenter study performed by 6 hospital pharmacists in Spain. The primary outcome was the proportion of treatment adherence as evaluated by pill reconciliation during the 3-month active follow-up period. Those with an adherence > 80% were categorized as adherent. We performed multivariate Cox regression analyses to explore the factors associated with progression-free survival. Results From December 2019 to November 2022, we recruited 95 evaluable patients. Most of the patients received osimertinib (n = 45, 45.3%) or a first- or second-generation tyrosine kinase inhibitor (n = 23, 34.8%). Eighty-one patients showed greater than 80% adherence (85.3%, 95% CI 78.1% to 92.4%), as evaluated based on pill reconciliation; the mean (SD) adherence to OAT was 94.7% (11.4). According to the univariate analysis, the time to progression from study entry was significantly shorter among patients who were nonadherent than among those who were adherent (median 6.5 months vs. not reached, log-rank test p = 0.006; hazard ratio [HR] 2.619, 95% confidence interval [CI] 1.240–5.532). In the multivariate Cox regression analysis, nonadherence was the single factor associated with progression-free survival. Conclusion Consistent with previous evidence in this setting, our results suggest that adherence to oral antineoplastic treatment among patients with NSCLC is high. Whether this high rate of adherence translates to better clinical outcomes should be further evaluated in larger samples.